Reabilitação Psicossocial e Recovery: conceitos e influências nos serviços oferecidos pelo Sistema de Saúde Mental / Psychosocial Rehabilitation and Recovery: concepts and influences in the services offered by Mental Health System - Anastácio, Camila Cardoso; Furtado, Juarez Pereira (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2013)
A concepção de reabilitação psicossocial sustenta a prática de grande parte dos profissionais de saúde mental no Brasil e no mundo.O advento da noção de recovery parece colocar em perspectiva e abrir novos horizontes em torno da reabilitação psicossocial. Objetivos: Identificar a concepção de reabilitação psicossocial vigente entre os trabalhadores de saúde mental; discutir convergências, divergências e compreender as noções de recovery e reabilitação psicossocial. Metodologia: Revisão e discussão de literatura, suficiente para definir ambos os conceitos e relacioná-los entre si. Aplicação de questionário para identificar, entre os profissionais de saúde mental, princípios do recovery presentes na prática de acompanhamento cotidiano de usuários de CAPS III. Resultados: Concluímos que o conceito de recovery da doença mental, quando utilizado para orientar os serviços pode trazer grande benefício para o usuário, possibilitando maior participação e autonomia. Porém, as concepções de garantia de direitos, trabalho e educação não se mostram ainda presentes dentre os trabalhadores. ABSTRACT: Introduction: The conception of psychosocial rehabilitation sustains the practice of the majority of professionals on mental health in Brazil and in the world. The notion of recovery seems to put into perspective and open new horizons to psychosocial rehabilitation. Objectives: Identify the conception of psychosocial rehabilitation current among the mental health professionals; discuss convergences, divergences and understand notions of recovery and psychosocial rehabilitation. Methodology: Review and discussion of literature, enough to define both concepts and relate them. Utilization of a questionnaire to identify, among mental health professionals, the principles of recovery in the practice of daily follow-up care of users of CAPS III. Results: We concluded that the concept of recovery in mental health when used to guide the services can bring great benefits to the users, allowing a wider participation and autonomy. Nevertheless, the concepts of rights, work and education guarantee do not show themselves present among the staff. KEYWORD: Psychosocial Rehabilitation. Recovery. Services. Mental health.